10-Gb/s limiting amplifier and laser - Galal, S. (IEEE Journal of solid state circuits)
A limiting amplifier incorporates active feedback, inductive peaking, and negative Miller capacitance to achieve a voltage gain of 50 dB, a bandwidth of 9.4 GHz, and a sensitivity of 4.6 mVpp for a bit-error rate of 10-12 while consuming 150 mW. A driver employs T-coil peaking and negative impedance conversion to achieve operation at 10 Gb/s while delivering a current of 100 mA to 25-Ω lasers or a voltage swing of 2 Vpp to 50-Ω modulators with a power dissipation of 675 mW. Fabricated in 0.18-μm CMOS technology, both prototypes operate with a 1.8-V supply.